A magyar köztársaság kikiáltása 1918. november 16-án : szimbolikus helyfoglalás térben és időben - Vörös, Boldizsár (Közép-Európai Közlemények, 2009)
The proclamation of the Hungarian Republic on 16 November 1918: symbolic reservation in space and time. The study examines the proclamation ceremony of the Hungarian Republic as a group of symbolic actions taken for reservation of place, which was held after the bourgeois-democratic revolution on 16 November 1918. On the one hand the organizers and the participants of the ceremony performed such a reservation of place that indicated the new political situation by decorating the House of Parliament of Budapest and the surroundings, and by bringing out crowds here to represent „the people”. On the other hand the main speakers endeavoured to define the role of the new system in time as well, and they mentioned certain Hungarian historical figures as progenitors, involving those who participated in the Hungarian revolution and war of independence in 1848/1849. Nevertheless the organizers of the ceremonious marching in of the National Army headed by Miklós Horthy, which was held on 16 November 1919, applied similar elements for the event as in the case of the ceremony of 1918. In 1919 the organizers intended to demonstrate the counter-revolution and the reckoning with the spirit of the Hungarian revolutions of 1918 and 1919. Besides the specific cases, the analyses illustrate also in general that vast programmes, held for the purpose of symbolic reservation of place, can be directed against each other; even in a way that – or just to achieve the desired effect – they apply similar elements.